Modelo de un muelle de ballestas considerando la fricción entre hojas. // Laminated spring model considering the friction between leaves. - Rodríguez Matienzo, J.; Otero Pereiro, L. (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2006)
Se brinda un modelo de una ballesta por el MEF incluyendo el contacto y la fricción. El problema se convierte en no lineal y se resuelve por el método de Newton-Raphson como un problema de optimización con restricciones. Se hace un análisis de las condiciones iniciales y de contorno para alcanzar la solución en un tiempo razonable, dando una estrategia para calcular el valor del penalty. Se logra una buena correspondencia en tre los valores de desplazamiento reales y teóricos. Finalmente se hace el análisis modal del modelo. Palabras claves: Ballestas, contacto, vibraciones, MEF. _____________________________________________________________________________ Abstract: A finite element model of a real laminated spring under bending should include the phenomena of contact and friction between leaves, in order to obtain values of displacements, stresses, gap, etc. close to reality. Considering contact and friction leads to a non-linear problem, which must be solved using numerical methods (Newton-Raphson), resulting in a classic optimization problem with constraints. The success of solution depends strongly on boundary conditions and initial values. A strategy for determining penalty values in the case of a multi leaf bending problem is presented, allowing a good correspondence with real displacements. The non-linear behavior of the leaf spring suspension referred to spring rate is shown. The modal analysis also gave firsts natural frequencies in the usual span for trucks and semi-trailers. Key words: Laminated spring, contact, vibration.